Control of a tri-state boost converter - Chew, Wei Liang. (2011)
This report describes the design and implementation of a DC to DC tri-state boost converter. The user is able to customize and select what DC output to obtain from a given DC input which is smaller than the output. The DC-DC tri-state boost converter has an extra state, called the free-wheeling state, which will not affect the discharging cycle of the capacitor, thus allowing a faster response from the converter. Implementation of controllers, which forms part of the closed loop circuit will also be presented in this report. In addition, the design and implementation of the PWM (Pulse Width Modulator) will be presented as well. Experimental results are also presented in this report.